Agile-Based CRM System Development to Improve Customer Satisfaction in Cargo Companies - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research highlights the problem of increasing competition and customer expectations in the cargo industry, which demands respon-sive and innovative solutions to improve customer satisfaction. In the face of these challenges, the research used the Agile approach in de-veloping a Customer Relationship Management (CRM) system as an appropriate solution. The research method involves user requirements analysis, iterative system development, and comprehensive functional testing. The results show that implementing a CRM system based on the Agile approach can improve customer service efficiency, personal-ize customer interactions, and improve decision-making. The contribu-tion of this research lies in proposing an approach that can be applied in the context of the cargo industry to improve customer satisfaction, as well as providing practical insights for cargo companies in design-ing and implementing effective CRM systems in a competitive environ-ment.